Evaluating concepts for short-term control in financial service processes - Dustin Behley; Michael Leyer (Frankfurt School of Finance & Management, 2011)
Financial services are characterised by the integration of customers while the service is being delivered. This integration leads to interruptions and thus delays in the processing of a customer order until for example the customer provides the missing input. Because customer behaviour can only be planned to a certain extent this is a major problem for an efficient control of financial service processes. It would be helpful to know which concept leads to the best solution for a certain situation in controlling the process. A concept contains explicit practical knowledge e.g. using a stand-by-employee or a prioritisation of customer orders with first-infirst-out. As financial services differ from manufacturing processes application knowledge of concepts cannot be transferred one to one. To test concepts regarding their ability to deal efficiently with interruptions by customers short-term simulations should be conducted. Shortterm simulation uses the actual state of a process and is not focussing on steady-state results. The research presented focuses on comparing several concepts for short-term control using case-study data of a typical financial service process. For this process a simulation model is built based on process mining. This approach is used to gather information out of documented timestamps of underlying process-aware information systems. Such timestamps allow a historical analysis to build typical scenarios and to gather the actual state of a financial service process as a starting point for a simulation analysis. The depicted concepts are simulated for different typical scenarios points to determine respectively which concept suits best. The results show which concepts suit best in certain situations for the case study conducted.
Keywords: C63; D24; G20; M11; 330; short-term control; financial services; business process simulation